Investigating interactive methods in remote chestfeeding support for lactation consulting professionals in Brazil - Jessica de Souza; Cinthia Calsinski; Kristina Chamberlain; Franceli Cibrian; Edward Jay Wang (Frontiers Media S.A., 2023)
ObjectiveLactation consultants (LCs) positively impact chestfeeding rates by providing in-person support to struggling parents. In Brazil, LCs are a scarce resource and in high demand, risking chestfeeding rates across many communities nationwide. The transition to remote consultations during the COVID-19 pandemic made LCs face several challenges to solve chestfeeding problems due to limited technical resources for management, communication, and diagnosis. This study investigates the main technological issues LCs have in remote consultations and what technology features are helpful for chestfeeding problem-solving in remote settings.MethodsThis paper implements qualitative investigation through a contextual study (n=10) and a participatory session (n=5) to determine stakeholders' preferences for technology features in solving chestfeeding problems.FindingsThe contextual study with LCs in Brazil characterized (1) the current appropriation of technologies that help during consultations, (2) technology limitations that affect LCs' decision-making, (3) challenges and benefits of remote consultations, and (4) cases that are easy and difficult to solve remotely. The participatory session brings LCs' perceptions on (1) components for an effective remote evaluation, (2) preferred elements by professionals when providing remote feedback to parents, and (3) feelings about using technology resources for remote consultations.ConclusionFindings suggest that LCs adapted their methodologies for remote consultations, and the perceived benefits of this modality show interest in continuing to provide remote care as long as more integrative and nurturing applications are offered to their clients. We learned that fully remote lactation care might not be the main objective for overall populations in Brazil, but as a hybrid mode of care that benefits parents by having both modalities of consultations available to them. Finally, remote support helps reduce financial, geographic, and cultural barriers in lactation care. However, future research must identify how generalized solutions for remote lactation care can be, especially for different cultures and regions.